THE RELATIONSHIP BETWEEN DIET COMPLIANCE AND CHANGES IN BLOOD SUGAR LEVELS OF DIABETES MELLITUS PATIENTS IN THE WORK AREA OF HIANG COMMUNITY HEALTH CENTER IN KERINCI REGENCY IN 2024 - Gusnaini, Ema; Soviarni, Soviarni; Herlina, Devfi (Jurnal Keperawatan Universitas Jambi, 2024)
Diabetes Mellitus is a complex chronic disease that occurs due to abnormalities in insulin secretion, insulin action, or both, causing the body to experience disturbances in the metabolism of carbohydrates, proteins, and fats which results in blood glucose levels tending to increase or hyperglycemia. This research aims to determine the relationship between diet adherence and changes in blood sugar levels of diabetes mellitus patients in the Hiang Community Health Center working area, Kerinci Regency in 2024. This research uses a correlational quantitative research design. The sample in this study was 31 respondents and sampling took 10-15% of the total population. The independent variable is diet compliance, while the dependent variable is blood sugar levels. Statistical tests use the Chi-Square test. The results of the study showed that there were 15 respondents (48.4%) who adhered to their diet and 14 respondents (45.2%) changed blood sugar levels in diabetes mellitus patientsto normal. The Chi-Square statistical test shows that the P value = 0.007 <α = 0.05, which means Ha is accepted. This research concludes that there is a relationship between Diet Compliance and changes in blood sugar levels of diabetes mellitus patients in the Working Area of the Hiang Community Health Center, Kerinci Regency in 2024. It ishoped that diabetes mellitus patients and their families will know that to achieve normal blood sugar levels, they need to increase dietcompliance. Suggestions for authors are expected to increase insight, knowledge, and skills, and for educational institutions, it is hoped that they can provide information and scientific expertise for students of the Bina Insani Sakti Nursing Academy regarding the relationship between diet compliance and changes in blood sugar levels in diabetes mellitus patients, for the community health center, it is hoped that the community health center will provide education and information to diabetes mellitus patients, meanwhile, it is expected that future researchers who will research the same theme can develop this research with other independent variables.